Harmful Algal Bloom Toxicity in Lithobates catesbeiana Tadpoles - Robin C. Su; Casey M. Meyers; Emily A. Warner; Jessica A. Garcia; Jeanine M. Refsnider; Apurva Lad; Joshua D. Breidenbach; Nikolai Modyanov; Deepak Malhotra; Steven T. Haller; David J. Kennedy (Toxins, 2020)
Harmful algal blooms (HAB) have become a major health concern worldwide, not just to humans that consume and recreate on contaminated waters, but also to the fauna that inhabit the environments surrounding affected areas. HABs contain heterotrophic bacteria, cyanobacterial lipopolysaccharide, and cyanobacterial toxins such as microcystins, that can cause severe toxicity in many aquatic species as well as bioaccumulation within various organs. Thus, the possibility of trophic transference of this toxin through the food chain has potentially important health implications for other organisms in the related food web. While some species have developed adaptions to attenuate the toxic effects of HAB toxins, there are still numerous species that remain vulnerable, including Lithobates catesbeiana (American bullfrog) tadpoles. In the current study we demonstrate that acute, short-term exposure of tadpoles to HAB toxins containing 1 µg/L (1 nmol/L) of total microcystins for only 7 days results in significant liver and intestinal toxicity within tadpoles. Exposed tadpoles had increased intestinal diameter, decreased intestinal fold heights, and a constant number of intestinal folds, indicating pathological intestinal distension, similar to what is seen in various disease processes, such as toxic megacolon. HAB-toxin-exposed tadpoles also demonstrated hepatocyte hypertrophy with increased hepatocyte binucleation consistent with carcinogenic and oxidative processes within the liver. Both livers and intestines of HAB-toxin-exposed tadpoles demonstrated significant increases in protein carbonylation consistent with oxidative stress and damage. These findings demonstrate that short-term exposure to HAB toxins, including microcystins, can have significant adverse effects in amphibian populations. This acute, short-term toxicity highlights the need to evaluate the influence HAB toxins may have on other vulnerable species within the food web and how those may ultimately also impact human health.